The changing molecular epidemiology of HIV-1 in Liangshan prefecture, China, in 2021–2023 - Pei, Rong; Su, Ling; Jike, Chunnong; Yu, Gang; Wang, Ju; Xiao, Lin; Wang, Yubing; Shen, Maogang; Zhou, Chang; Liao, Jiayi; Zhang, Yulian; Zheng, Yifei; et al. (Frontiers in Microbiology, 2025)
IntroductionLiangshan Prefecture is one of the areas in China most severely affected by human immunodeficiency virus (HIV), but little is known about the molecular epidemiology of HIV-1 in this area. We aimed to analyze the distribution of HIV-1 genetic variants in Liangshan Prefecture in recent years.Methods8,523 blood samples were collected from people living with HIV with treatment failure and newly diagnosed individuals in all 17 counties and cities in Liangshan Prefecture between 2021 and 2023.ResultsThe majority of study participants were male (66%), farmers (78%) and illiterate (53%). The main HIV-1 transmission routes were heterosexual contact (57%) and injecting drug use (27%). Among the 6,298 successfully obtained pol sequences the following HIV-1 variants were identified: CRF07_BC (93.9%), CRF08_BC (3.3%), CRF01_AE (1.4%), URFs (0.9%), CRF105_0108 (0.1%), CRF55_01B (0.1%), subtype B (0.1%), subtype C (0.1%), CRF88_BC (0.1%), CRF83_cpx (0.1%), CRF85_BC (0.03%), CRF67_01B (0.02%), CRF77_cpx (0.02%), and subtype A (0.02%). During the study period, the proportion of CRF07_BC gradually decreased, while other HIV-1 variants increased, a shift seen across all counties in Liangshan Prefecture. Newly diagnosed patients mainly acquired HIV through heterosexual transmission (86.7%), had a lower proportion of CRF07_BC (90.9%) and higher proportion of other HIV-1 variants, compared to treatment failure patients.ConclusionFuture prevention and control policies need to take these changes into account.